Engineered bacterial host for genetic encoding of physiologically stable protein nitration - Koch, Nikolaj G.; Baumann, Tobias; Nickling, Jessica H.; Dziegielewski, Anna; Budisa, Nediljko (Frontiers in Molecular Biosciences, 2022)
Across scales, many biological phenomena, such as protein folding or bioadhesion and cohesion, rely on synergistic effects of different amino acid side chains at multiple positions in the protein sequence. These are often fine-tuned by post-translational modifications (PTMs) that introduce additional chemical properties. Different PTMs can be genetically encoded and precisely installed by expanding the genetic code at single or multiple sites. Protein nitration is a PTM of particular interest because it has been associated with several diseases. However, even when these nitro groups are directly incorporated into proteins, they are often physiologically reduced during or shortly after protein production. We have solved this problem by using an engineered Escherichia coli host strain. We removed six genes from the genome that are associated with nitroreductase activity in a simple and robust manner. The result is a bacterial expression host that can stably produce proteins and peptides containing nitro groups, especially when these are amenable to modification. To demonstrate the applicability of this strain, we used this host for several applications. One of these was the multi-site incorporation of a photocaged 3,4-dihydroxyphenylalanine derivative into Elastin-Like Polypeptides. For this non-canonical amino acid (ncAA) and several other photocaged ncAAs, the nitro group is critical for photocleavability. Accordingly, our approach also enhances the production of biomolecules containing photocaged tyrosine in the form of ortho-nitrobenzyl-tyrosine. We envision our engineered host as an efficient tool for the production of custom designed proteins, peptides or biomaterials for various applications ranging from research in cell biology to large-scale production in biotechnology.